Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Penggunaan Karu Kredit Pada Pegawai Negeri Sipil SKPD Kabupaten Kutai Kartanegara - Putri Anggraeni; Justina Ade Judiarni; Muhammad Amin Kadafi (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to determine The Influence of Financial Literacy and Behavioral Finance Partially to Using Credit Card in Government Employees SKPD District Kutai Kartanegara. Sampling in this research using nonprobability sampling method, by using purposive sampling technique in which the selected sample is based on certain criteria. The sample used is Government Employees SKPD District Kutai Kartanegara. The number of samples used is 100 respondents. Data analysis method used is Multiple Linear Regression using SPSS version 23. The results of this study indicate that the variable Financial Literacy partially have a significant positive effect on Using Credit Card in Government Employees SKPD District Kutai Kartanegara. However variable Behavioral Finance partially not have a significant positive effect on Using Credit Card in Government Employees SKPD District Kutai Kartanegara.